Solidifikasi Logam Berat Cu(II) Pada Limbah Cair (Lumpur Berminyak dan Oli Bekas) Dengan Menggunakan Semen Portland - Fany Fahran Jany; Jon Efendi (Jurnal Periodic Jurusan Kimia UNP, 2020)
Abstract- Very rapid development of the industry has led to increased levels of heavy metals in the environment. Heavy metals are the main group of inorganic pollutants that can contaminate wastewater in the environment. One of them is copper metal (Cu). Copper metal has a reddish brown color. This metal is very poisonous, and in high concentrations it can interfere with human health, such as damaging the respiratory system, mental disorders in children, cancer, death, and so on. This can be anticipated in various ways, one of which is the Solidification Method. The principle of the solidification method is to bind compounds in hazardous waste into insoluble / solid form and trap the waste in solids. The paramenter analysis used is the TCLP (Toxicty Characteristic Leaching Out Procedure) test. From the research data, it was found that the highest concentration of oily sludge was 0.19 mg / L and the lowest was 0.15 mg / L. In used oil waste, the highest concentration is 1.6 mg / L. From the solidification results of oily sludge and used oil waste, it can be concluded that the value of oily sludge waste is smaller than used The oil waste, and it can still be said to be safe to dispose of into the environment. The higher the cement solidification in the sample test, the higher the Cu content in the sample.